OVERCOMING THE PROBLEMS OG HEUVEL TRIBE OFFLINE STORE BASED ON 4P MARKETING AND IMPLEMENTING THE TEACHINGS OF TAMANSISWA - Legiman; Ratnasari, Ayu; Fatoni, Rizal; of Ramadan, Star; Amandasari, Adellia; Kencana Dewi, Nawang; Dwi Cahya, Agus; Siripipatthanakul, Supaprawat (SMARTINDO, 2024)
This community service program aims to apply the values taught by Ki Hadjar Dewantara Ngandel (trust), Kendel (courage), Bandel (perseverance), and Kandel (resilience) to improve the performance of the